YOU CAN NOT BUY THE TIME THAT YOU WASTE. - Ashurova Gulbeka Alisher qizi (TADQIQOTLAR.UZ, 2024)
Managing your time effectively and working efficiently in your role can help you accomplish more on a day-to-day basis. While most professionals are aware of how important it is to avoid wasting time at work, it can be challenging to do so. If you're struggling with your productivity levels, it may be helpful for you to identify strategies for overcoming time-wasters. In this article, we outline why it's important to avoid time-wasters in the workplace and list nine common environmental and personal factors that contribute to wasted time, including tips on how you can avoid them.